Effect of Green Marketing and Word of Mouth on Starbucks Indonesia Consumer Buying Decisions with Brand Image as Intervening Variable - Yudha Ari Wibowo; Ririn Wulandari (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2022)
This study aims to analyze Green Marketing and Word of Mouth on Starbucks Indonesia Consumer Buying Decisions through Brand Image as Intervening. The population analyzed is millennial consumers who buy Starbucks products in Jakarta and have jobs. The samples analyzed were 170 respondents. Through SEM PLS analysis, it was found that Green Marketing had a significant impact on Brand Image, Word of Mouth had a significant impact on Brand Image, Green Marketing had a significant impact on Buying Decisions, Word of Mouth had a significant impact on Buying Decisions, Brand Image had a significant impact on Buying Decisions, Brand Image has the ability to intervene Green Marketing and Word of Mouth on Buying Decisions, But unable to strengthen.